WEB-SPLINE PREDICTION OF OCULAR SURFACE TEMPERATURE USING BIOHEAT EQUATION WITH EXTERNAL SOURCE EXPOSURE - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2014)
In this paper, the finite element method (FEM) with web-spline computer modeling were applied to study corneal surface temperature increase during microwave irradiation. The heat conduction model of the microwave-irradiated eye, which assumed to be 3D, was constructed. The mechanism of heat transfer from the eye and the selection of the thermal parameters of the media of the eye are also discussed. The implementation of these parameters in the web-spline solution of heat conduction was then developed. Furthermore, temperature rise calculations were compared with the values found in the literature pertaining to microwave-induced cataract formation.
Keywords: Bioheat transfer model; microwave irradiation; web-spline; HUMAN EYE; MODEL; INCREASE; ANTENNA; WAVES; RISES; FIELD; SAR